FRI0430 Effect of oral nutritional intervention on nutritional status in patients with systemic sclerosis. (12th June 2018) - Wojteczek, A.; Ziętkiewicz, M.; Małgorzewicz, S.; Zdrojewski, Z.
Abstract : Background: Patients with systemic sclerosis (SSc) are at risk of malnutrition, which ranges from 18% to 56% of cases. 1, 2 The high impact of nutritional status on clinical outcome has been shown for many diseases. The optimal nutritional treatment can lead to improvement or preservation of the current nutritional status and increases probability of long-term survival. 3 Objectives: The aim of the study was to determine whether nutritional support has an impact on improvement of nutritional status in SSc patients. Methods: The study included 61 patients with SSc and 49 healthy adults. Nutritional status was determined with subjective global assessment (SGA), body mass index (BMI), bioelectrical impedance analysis (BIA) and anthropometric measurements. Nutrition-related laboratory tests were measured. Appetite was assessed by simplified nutritional appetite questionnaire (SNAQ). Results: Impaired nutritional status was confirmed in 16 patients with SSc (26, 2%). Those patients had significantly lower SGA, BMI (p=0, 0019), hand grip strength (p=0, 0019), appetite (p=0, 019) and BIA parameters such as lean tissue mass (p=0, 013), intracellular water (p=0, 0006), adipose tissue mass (p=0, 04). In laboratory tests levels of haemoglobin, albumin and HDL cholesterol were significantly lower, while erythrocyte sedimentation rate (ESR) was higher (p=0, 0025). Thirteen patients had dietary intervention (high-energy, high-protein, oral, liquid nutritional supplements) for 12 weeks. SGA (p=0, 017) and hand grip strength (p=0, 006) improved after nutritional treatment. BMI, appetite, BIA parameters, lipid profile and ESR after 12 weeks remained stable. Conclusions: Assessment of nutritional status in SSc patients should be performed regularly, because inclusion of oral nutritional intervention may improve SGA and hand grip strength. References: [1] Baron M, et al. Malnutrition is common in systemic sclerosis: results from the Canadian scleroderma research group database. J Rheumatol2009;36:2737–43. [2] Krause L, et al. Nutritional status as marker for disease activity and severity predicting mortality in patients with systemic sclerosis. Ann Rheum Dis2010;69:1951–1957. [3] Harrison E, et al. Long-term outcome of patients with systemic sclerosis requiring home parenteral nutrition. Clinical Nutrition2015;34:991–996. Disclosure of Interest: None declared